Impact of mothers' employment on infant feeding and care: a qualitative study of the experiences of mothers employed through the Mahatma Gandhi National Rural Employment Guarantee Act. Issue 4 (2nd April 2014) - Nair, Manisha; Ariana, Proochista; Webster, Premila
Abstract : Objective: To explore the experiences of mothers employed through the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) using focus group discussions (FGDs) to understand the impact of mothers' employment on infant feeding and care. The effects of mothers' employment on nutritional status of children could be variable. It could lead to increased household income, but could also compromise child care and feeding. Setting: The study was undertaken in the Dungarpur district of Rajasthan, India. Participants: Mothers of infants <12 months of age. Ten FGDs, two in each of the five administrative blocks of the study district were conducted. The groups were composed of a minimum of 5 and maximum of 8 participants, giving a total of 62 mothers. Thematic analysis was conducted to assess patterns and generate emergent themes. Results: Four major themes were identified—'mothers' employment compromises infant feeding and care', 'caregivers' inability to substitute mothers' care', 'compromises related to childcare and feeding outweigh benefits from MGNREGA' and 'employment as disempowering'. Mothers felt that the comprises to infant care and feeding due to long hours of work, lack of alternative adequate care arrangements, low wages and delayed payments outweighed the benefits from the scheme. Conclusions: This study provides an account of the trade-off between mothers' employment and child care. It provides an understanding of the household power relationships, societal and cultural factors that modulate the effects of mothers' employment. From the perspective of mothers, it helps to understand the benefits and problems related to providing employment to women with infants in the MGNREGA scheme and make a case to pursue policy changes to improve their working conditions.